Respuesta :

Answer:

Step-by-step explanation:

22) J(2,-1); K(2,5)

Distance = √(x₂-x₁)² + (y₂-y₁)²

                = √( 2- 2)² + (5 - [-1] )²

                = √0 + (5  + 1 )²

                =√ ( 6 )²   = 6

25) A(0,3) ; B (0,12)

distance =√(0-0)² + (12 - 3 )²

              =√( 9)²  = 9

28) Q(12,-12) ; T(5,12)

distance = √(5 - 12)² + (12 - [-12] )²

              = √( -7)² + (12 + 12] )²

              = √ 49 + (24)²

              = √ 49 + 576

               = √625

                 =25